Analisis Peran Online Customer Review Dalam Memediasi Hubungan Online Customer Rexperience Terhadap Peningkatan Marketplace Rating - Utami Qaulan Tsaqila; Asep Muhamad Ramdan; Resa Nurmala (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Marketplace is one of the impacts from development of e-commerce systems in the world. Marketplace are in great demand by all types of groups because they are able to increase the effectiveness and efficiency of users in shopping online. Starting from the choice of goods with various prices, brands, quality, to easy and fast transaction and shipping processes. However, along with its development, competition between marketplace companies has become increasingly stringent, causing several companies to experience a decline due to newcomers offering new experiences. This research was made with the aim of knowing the extent to which the influence of online user experience (online customer experience) in increasing marketplace ratings through online customer reviews as a mediating variable. Quantitative research method with proportional random sampling technique is the research method used for this research. Data collection was carried out by distributing questionnaires to 250 respondents consisting of students who have used the Bukalapak application from each tertiary institution in the city of Sukabumi. The data analysis technique in this study used structural equation modeling (SEM) using AMOS software version 22. The final results of the study showed that there was a positive influence from online customer reviews in mediating the relationship between online customer experience and marketplace rating. Ratings on companies can increase if they succeed in creating the best experience for users after using online shopping applications. Keywords: Marketplace, Marketplace Rating, Online Customer Experience, Online Review